A prospective study of adverse drug reactions to antiepileptic drugs in children. Issue 6 (1st June 2015) - Anderson, Mark; Egunsola, Oluwaseun; Cherrill, Janine; Millward, Claire; Fakis, Apostolos; Choonara, Imti
Abstract : Objectives: To prospectively determine the nature and rate of adverse drug reactions (ADRs) in children on antiepileptic drugs (AEDs) and to prospectively evaluate the effect of AEDs on behaviour. Setting: A single centre prospective observational study. Participants: Children (<18 years old) receiving one or more AEDs for epilepsy, at each clinically determined follow-up visit. Primary and secondary outcomes: Primary outcome was adverse reactions of AEDs. Behavioural and cognitive functions were secondary outcomes. Results: 180 children were recruited. Sodium valproate and carbamazepine were the most frequently used AEDs. A total of 114 ADRs were recorded in 56 of these children (31%). 135 children (75%) were on monotherapy. 27 of the 45 children (60%) on polytherapy had ADRs; while 29 (21%) of those on monotherapy had ADRs. The risk of ADRs was significantly lower in patients receiving monotherapy than polytherapy (RR: 0.61, 95% CI 0.47 to 0.79, p<0.0001). Behavioural problems and somnolence were the most common ADRs. 23 children had to discontinue their AED due to an ADR. Conclusions: Behavioural problems and somnolence were the most common ADRs. Polytherapy significantly increases the likelihood of ADRs in children. Trail registration number: EudraCT (2007-000565-37).